Mineral composition, histomorphometry, and bone biomechanical properties are improved with probiotic, prebiotic, and symbiotic supplementation in rats chronically exposed to passive smoking: a randomized pre-clinical study - Tribst,Marcelo Fernandes (2019)
ABSTRACT: Cigarette smoke in large centers is one of the most important causes of chronic inflammatory diseases in public health and is associated with a decrease in bone mass, consolidation process, and bone remodeling. Due to their ability to improve intestinal absorption and compete with pathogenic microorganisms, dietary supplementation with functional foods may contribute to improvement in bone quality. Therefore, the objective of this study was to evaluate the effects of functional, probiotic, prebiotic, or symbiotic food supplementation on mineral composition, histomorphometry, and bone biomechanical properties of rats in the growth phase, chronically exposed to cigarette smoke (T).Sixty-four young male rats were randomly assigned to eight groups (n=8): control (C) [standard diet (SD)]; probiotic (Pro) [SD + probiotic (Lactobacillus acidophilus, Enterococcus faecium, Bifidobacterium thermophilum and Bifidobacterium longum) (2-5 109 UFC each)]; prebiotic (Pre) [SD+ prebiotic (mannan oligosaccharide)]; symbiotic (Sym) (SD + probiotic + prebiotic); control smoking (SC) [(SD + exposure protocol to passive smoking (PS)]; probiotic smoking (ProS) (SD + probiotic + PS); prebiotic smoking (PreS) (SD + prebiotic + PS), and symbiotic smoking (SymS)(SD + prebiotic + probiotic + PS). The animals were euthanized after 189 days of the experimental protocol. Results showed that supplementation with probiotics, prebiotics, and symbiotics significantly improved (P<0.05) the parameters: P, Ca, Mg, BMD, BMC, strength, resilience, and size of area of the femoral diaphysis of the animals chronically exposed or not cigarette smoke. We concluded that functional food supplementation improved the bone health of rats chronically exposed or not to cigarette smoke.